2019
DOI: 10.1159/000502997
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia Nervosa and Autism Spectrum Disorders: Future Hopes Linked to Mucosal Immunity

Abstract: Mental health is becoming a public health priority worldwide. Anorexia nervosa and autism spectrum disorders are 2 important types of childhood disorders with a bad prognosis. They share cognitive impairments and, in both cases, the microbiota appears to be a crucial factor. Alteration of the microbiota-gut-brain axis is an appealing hypothesis to define new pathophysiological mechanisms. Mucosal immunity plays a key role between the microbiota and the brain. The mucosal immune system receives and integrates m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…IgA antibodies are primarily products of mucosal cellular immune response. Patients with AN often suffer from various GIT disorders, and thus the mucosal immunity and IgA production may be affected ( 37 , 38 ). However, total serum IgA levels were determined to be similar in patients with AN and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…IgA antibodies are primarily products of mucosal cellular immune response. Patients with AN often suffer from various GIT disorders, and thus the mucosal immunity and IgA production may be affected ( 37 , 38 ). However, total serum IgA levels were determined to be similar in patients with AN and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…To date, it is widely recognized that nutritional deficiencies, malnutrition and starvation impair the human immune system, affecting cell-mediated immunity [13,14], as reflected by the depletion of leukocyte, lymphocyte and T-cell counts in restricting-type AN subjects without modifications of B cells [15,16]. Even though preliminary evidence demonstrated that AN was associated with immune system deficit, data regarding inflammatory alterations in patients affected by AN are still contrasting [17]. Notably, some authors pointed out that patients with AN, although severely malnourished, are relatively free from presenting an increased risk of common viral infections [15,18], suggesting that the adaptation process occurring in this disorder is multifaceted and worth studying.…”
Section: Introductionmentioning
confidence: 99%
“…Microbiota is also known for its crucial role in modulating the immune response, including cytokine levels, exerting proinflammatory or anti-inflammatory activities depending on its compositions [19]. Many authors hypothesized a possible biunivocal influence between microbiota and the CNS through the immune system [19,61]. The case of Mr. XY seems in line with these hypotheses, showing the presence, at the same time, of autistic symptoms, AN, and BS, a disease linked to altered immune response.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, while, as stated above, both autism spectrum and AN were reported to be associated with immune system alterations, scant literature focused on the concomitant occurrence of these three conditions. A recent review further remarked the link between ASD, AN, specific immune alterations, and microbiota profiles, suggesting that future researches in the field of immunopsychiatry should focus on mucosal immunity [61]. Within an integrative framework between central and peripheral systems, more clinical research is needed to clarify the link between neurodevelopment, immune system, and eating disorders.…”
Section: Discussionmentioning
confidence: 99%